Pengembangan Masyarakat Desa Terpadu Berbasis Potensi Lokal di Jambean Kalibeber Mojotengah Wonosobo - Agus Riyadi; M. Mudhofi; Nur Hamid; Hatta Abdul Malik (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Development which has been oriented towards the growth paradigm so far has been applied in Indonesia, apart from having produced a number of significant changes, there have also been a number of dark portraits that have contributed to worsening the image of development with the above orientation. The benefits of development are more widely felt by the upper strata of society, so that the gap in social and economic inequality is widening. The growth orientation only encourages the development of large-scale businesses and industries, resulting in a widening gap between small and micro scale enterprises (SMEs) and large medium enterprises (UMB). This Lecturer Service Work aims to provide assistance to the community in Jambean Kalibeber Mojotengah Wonosobo based on local potential. The implementation of the Lecturer Service Work program uses the following approaches: a group-based approach and a family-based approach. The results of the dedication show that: 1) community development work is not an ad hoc activity, but an ongoing activity, so as to build productive and sustainable social cohesiveness in the long term, 2) Integrated village community development is an effort to carry out social change that emphasizes multi sectoral, by prioritizing local participation and bottom-up planning